Sufism in Saudi Arabia since 1979 : The Politics of Orthodoxy in Contemporary Islam - Sinani, Besnik, (Middle East and Islamic Studies E-Books Online, Collection 2026., 2026)
This is the first full-length monograph to explore Sufism in Saudi Arabia since 1979-a groundbreaking journey into a rarely seen side of the kingdom's religious life. Drawing on rich fieldwork, in-depth interviews with Sufi practitioners, and archival research, the book brings readers deep into the spiritual networks that persist beneath the surface of state-enforced Wahhabi orthodoxy. It traces a century of scholarly life in the Hejaz, follows transnational ties-especially those of the Ba ʿAlawi order-and uncovers stories of persecution, such as that of Muhammad Alawi al-Maliki. Timely and vivid, it also examines the profound religious shifts unfolding under the rule of Mohammed bin Salman.